The spread of raised (ay) and (aw) in Yami: From regional distinctiveness to ethnic identity marker. Issue 2 (17th April 2019) - Lai, Li-Fang; Gooden, Shelome
Abstract : This article extends previous analyses on (ay) and (aw) raising in Yami, an endangered Austronesian language spoken on Orchid Island, Taiwan. Two patterns of (ay) and (aw) variation co-exist in Yami—the more conservative/unraised variants and the innovative/raised forms—each of which indexes an authentic regional identity. Results from recent data suggest that Yami has undergone significant changes in just one generation as the raised variants are now preferred by younger islanders and have started permeating through non-raising areas. Traumatic shifts in the ecological context on Orchid Island help explain this sound change. Economically, rapid shift from fishing/farming to tourism trades promotes daily face-to-face communications among younger islanders, which has catalyzed the spread of nucleus raising to non-raising areas. Sociopsychologically, ongoing intergroup conflicts between islanders and mainland Taiwanese may further trigger the sound change, altering nucleus raising into a new communal system which highlights Yami identity in opposition to Others.